IOT Based Smart Health Care - Navya Teja, Yalamanchili; Vooha, Lavu; Rohini Priya, Adusumilli; V.K.Ramesh, N (International Journal of Engineering and Technology, 2018)
As these days there is a lot of effect because of environmental pollution and other factors like work pressure human health problems are increasing to a maximum extent. Technology takes a major role in monitoring the health of a individual. This helps to have a copy of recorded values and this helps in taking immediate steps to cure the condition or a precautions needed. As it important to monitor some parameters of the patient we use some sensors. The bluetooth module helps in collecting data from the sensors and sends it to the mobile through Bluetooth and this data can be uploaded to the cloud using Mobile data. This gives perfect data for the doctors to take a decision and give a suggestion to the patient.Â Â Â